EFFECT OF STEAM METHOD ON PUPILS’ ACADEMICPERFORMANCE IN ILORIN SOUTH LOCAL GOVERNMENT AREA, KWARA STATE - Hafees Tosin Sulyman; Esther Damilola Emmanuel (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study examined the effect of STEAM method on pupils’ academic performance in Ilorin South Local Government, Kwara State. The study adopts a pre-test post-test control group quasi-experimental design due to the suitability in establishing possible effect relationship. The study was limited to four schools and factorial design of 2x2x2 was adopted to test the null hypotheses for this study. The research instrument used for data collection were STEAM instructional guide and Pupils Achievement Test which is specifically titled (PAT) with reliability index of r=0.91. Data were analyzed using descriptive statistic (frequency count, mean and percentage) for demographic data and inferential statistics (ANCOVA) was used to test the formulated hypotheses which were all tested at 0.05 level of significance. The findings revealed that there was significant main effect of STEAM method on pupils’ academic performance (F (1; 69) = 23.934, P< 0.05). There was no significant interaction effect of treatment and school type on pupils’ academic performance (F (1; 69)=.240; P > 0.05). and also There was no significant interaction effect of treatment and gender on pupils’ academic performance (F (1; 69)=.683; P > 0.05). Based on these findings the following conclusions were drawn from this study, it is evident that STEAM method has main effect on the academic performance. STEAM method can bring about improvement in the academic performance of pupils regardless of gender. It was highly recommended that Nigerian Teachers in general should adopt it in their classroom interaction. Teachers should not limit their knowledge to what they were taught while in training they should be current and updated with latest strategies. Through this, they will be equipped with more knowledge that will improve pupils’ academic performance.